Improving agricultural publishing capabilities in ACP countries - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1991)
A great deal of valuable research is carried out in National Agricultural Research Systems (NARS) in developing countries, but too little reaches the people who can use it, such as other scientists who need to build on advances and innovations,...